Frequency of Developmental Dental Anomalies in the Indian Population - Guttal, Kruthika S; Naikmasur, Venkatesh G; Bhargava, Puneet; Bathi, Renuka J (European Journal of Dentistry, 2010)
Objectives: To evaluate the frequency of developmental dental anomalies in the Indian population.Methods: This prospective study was conducted over a period of 1 year and comprised both clinical and radiographic examinations in oral medicine and radiology outpatient department. Adult patients were screened for the presence of dental anomalies with appropriate radiographs. A comprehensive clinical examination was performed to detect hyperdontia, talon cusp, fused teeth, gemination, concrescence, hypodontia, dens invaginatus, dens evaginatus, macro- and microdontia and taurodontism. Patients with syndromes were not included in the study.Results: Of the 20,182 patients screened, 350 had dental anomalies. Of these, 57.43% of anomalies occurred in male patients and 42.57% occurred in females. Hyperdontia, root dilaceration, pegshaped laterals (microdontia), and hypodontia were more frequent compared to other dental anomalies of size and shape.Conclusions: Dental anomalies are clinically evident abnormalities. They may be the cause of various dental problems. Careful observation and appropriate investigations are required to diagnose the condition and institute treatment. (Eur J Dent 2010;4:263-269)
Keywords: Dental anomalies; Hyperdontia; Microdontia; Taurodontism